2017
DOI: 10.1186/s12914-017-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence against female university students in Ethiopia

Abstract: BackgroundThough many women are suffering the consequences of sexual violence, only few victims speak out as it is sensitive and prone to stigma. This lack of data made it difficult to get full picture of the problem and design proper interventions. Thus, the aim of this study was to assess the prevalence and factors associated with sexual violence among female students of Wolaita Sodo University, south Ethiopia.MethodsInstitution based cross-sectional study was conducted among 462 regular female Wolaita Sodo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
60
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 25 publications
17
60
4
4
Order By: Relevance
“…This was comparable to other mean ages reported in similar studies among students in higher institutions (Kamile, 2009;Hogue, 2011;Duru et al, 2015a;Mavhand-Madzusi and Asgedom, 2015;Akintayo et al, 2015;Adinew and Hagos, 2017). This fall within age range of youths and young adults which is the likely mean age of most university students.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This was comparable to other mean ages reported in similar studies among students in higher institutions (Kamile, 2009;Hogue, 2011;Duru et al, 2015a;Mavhand-Madzusi and Asgedom, 2015;Akintayo et al, 2015;Adinew and Hagos, 2017). This fall within age range of youths and young adults which is the likely mean age of most university students.…”
Section: Discussionsupporting
confidence: 73%
“…This figure was slightly higher than the country's national average of 17.6 years (National Population Commission, Nigeria). It was also higher than figures reported from similar studies among undergraduates in Ethiopia (Soboka and Kejela, 2015;Kassa et al, 2016;Adinew and Hagos, 2017). Nevertheless it was comparable findings in other of the reviewed studies (Hogue, 2011;Mulu et al, 2014;Akintayo et al, 2015;Toferra et al, 2015).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…A study conducted in Wolayta Sodo University indicated that 26% of the students who had multiple sexual partners and study conducted in New York on college aged students investigated that those who had multiple sexual partners were 65.6%. 16,17 This discrepancy of findings in different study area may be due to the difference in the socio-demographic characteristics.…”
Section: Discussionmentioning
confidence: 81%